2020
DOI: 10.1038/s41598-020-63237-8
|View full text |Cite
|
Sign up to set email alerts
|

Probing the structural evolution and electronic properties of divalent metal Be2Mgn clusters from small to medium-size

Abstract: Bimetallic clusters have aroused increased attention because of the ability to tune their own properties by changing size, shape, and doping. in present work, a structural search of the global minimum for divalent bimetal Be 2 Mg n (n = 1-20) clusters are performed by utilizing CALYPSO structural searching method with subsequent Dft optimization. We investigate the evolution of geometries, electronic properties, and nature of bonding from small to medium-sized clusters. it is found that the structural transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 60 publications
1
21
0
Order By: Relevance
“…A lot of studies on alkaline Earth metal magnesium clusters have been reported, in addition to usual studies of metal nanoclusters like gold, silver, and copper ( Köhn et al, 2001 ; Xia et al, 2016 ; Zhang et al, 2020 ; Zhao et al, 2021 ). This is partly because magnesium-based nanomaterials have an exceptional hydrogen storage capacity compared to ordinary materials ( Shao et al, 2012 ), and therefore, various kinds of Mg-based nanocluster materials, such as CoMg n ( Trivedi and Bandyopadhyay, 2015 ), RhMg n ( Trivedi and Bandyopadhyay, 2016 ), ScMg nanocluster ( Chen et al, 2020 ; Lyon, 2021 ), are worthy of systematic study.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of studies on alkaline Earth metal magnesium clusters have been reported, in addition to usual studies of metal nanoclusters like gold, silver, and copper ( Köhn et al, 2001 ; Xia et al, 2016 ; Zhang et al, 2020 ; Zhao et al, 2021 ). This is partly because magnesium-based nanomaterials have an exceptional hydrogen storage capacity compared to ordinary materials ( Shao et al, 2012 ), and therefore, various kinds of Mg-based nanocluster materials, such as CoMg n ( Trivedi and Bandyopadhyay, 2015 ), RhMg n ( Trivedi and Bandyopadhyay, 2016 ), ScMg nanocluster ( Chen et al, 2020 ; Lyon, 2021 ), are worthy of systematic study.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, based on the different quantum chemistry calculations, studies on metal-doped (Be, Al, Ge, Sn, 3 d and 4 d TM atoms) and nonmetal-doped (B, C, N, O, F and Si) magnesium clusters have harvested many great achievements [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. More importantly, based on the CALYPSO structural searching method and DFT, the structures and electronic properties of Be-, Be 2 -, Sr 2 - and Ba 2 -atom-doped differently sized magnesium clusters have been systemically discussed by Zeng’s, Zhao’s and our groups [ 33 , 34 , 35 , 36 , 37 ]. For example, Zeng and co-workers found that BeMg 9 0 , BeMg 9 +1 and BeMg 8 −1 clusters possess relative highly stability out of the studied systems [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research concluded that the position of Be atom changes from completely encapsulated sites to surface sites after reverting to the caged magnesium motif. Subsequently, the structures and electronic properties have been investigated for two Be-, Sr- and Ba-atom-doped small-sized magnesium clusters by our group [ 35 , 36 , 37 ]. For Be 2 Mg n ( n = 1–20) clusters, from n = 10, the structures transfer from 3 D to filled cage-like frameworks [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there has been an increasing amount of reports on using atomic clusters together with the first-principle to predict new stable nanomaterials as potential sensors (Ding et al, 2015;Jin et al, 2015Jin et al, , 2016Xia et al, 2016;Li et al, 2017;Chen et al, 2018;Shao et al, 2019;Zhao et al, 2019;Zhang et al, 2020) such as nanomaterials of Zr-B, Ta-B and Fe-O systems, etc. Nanomaterials of silicon and magnesium are inevitable and are studied through their clusters structures.…”
Section: Introductionmentioning
confidence: 99%